MORALIZING WAR AND CONSTRUCTING ENEMIES IN TRUMP’S 2025 IRAN SPEECH - Agwin Degaf; Hamadah Ashfiya (Department of English Literature, Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2025)
The growing intersection of political communication and ideological persuasion raises concerns about how language is used to legitimize state violence. Although previous research has addressed themes of populism and nationalistic rhetoric, limited attention has been given to how wartime speeches function as discursive practices that construct moral legitimacy for military intervention. Addressing this gap, this study investigates how Donald Trump’s June 2025 Iran speech constructs the enemy, moralizes war, and normalizes pre-emptive military violence. Using qualitative critical discourse analysis, the study examines both the transcript and delivery of the speech through Van Dijk’s socio-cognitive model of discourse, focusing on the ideological square and micro-level strategies such as actor description, metaphor, hyperbole, euphemism, presupposition, religious authority, victimization, and lexicalization. The findings show that the speech constructs a polarized moral framework in which the United States and its allies are represented as morally virtuous and divinely sanctioned, while Iran is framed as an irrational and existential threat. Military aggression is legitimized through hyperbolic glorification, religious invocation, euphemistic framing of destruction, and the strategic omission of civilian suffering, presenting war as a moral necessity rather than a political choice. While limited to a single case and not supported by corpus-based analysis, the study contributes to the literature on wartime political discourse by extending Van Dijk’s socio-cognitive model to contemporary conflict rhetoric and identifying a morally framed adaptation of the burden argument, shifting from economic to security and ethical justification. These findings underscore the ideological power of political language in shaping public consent for military action and highlight the need for sustained critical scrutiny of wartime political communication.